Jemadarius : uma WEB-API autoconfigurável para a internet das coisas - Barros, Eric Bernardes Chagas (2015)
Due to the fast growth of the Internet of Things, many concepts of distributed systems need to be adapted to this new paradigm. Concepts such as autonomic computing, context awareness and adaptability should be incorporated into devices, while maintaining the level of energy consumption and use of acceptable memory. They also need to receive support from larger and robust computer systems due to the large amount of data that needs to be transmitted in these pervasive computing systems. This work performs the implementation of an autonomic system emphasizing the self-configuration of devices and aided by cloud computing through a Web-API that was developed for this purpose. The results were obtained from tests performed on Z1 device with the help of the Contiki, running inside Cooja simulator. The results revealed that there is an overflow of the code developed for the tested devices, but with some adjustments you can get a good level of energy consumption and it is possible to reach the self-configuration of devices on the Internet of Things.